International Prostate Symptom Score (IPSS) Correlation with Sonographic Prostate Size - Ahmed, Awais; Khan, Muhammad Salman; Ahmed, Syed Naseer; Imran Farid, Muhammad; Inam, Qazi Adil; Ahmad, Irshad (Journal of Neonatal Surgery, 2025)
Introduction: The International Prostate Symptom Score (IPSS) is a broadly used questionnaire designed to assess the severity of lower urinary tract symptoms (LUTS) in men, particularly those related to harmless prostatic hyperplasia (BPH). Objectives: The basic aim to conduct this study is to find the International Prostate Symptom Score (IPSS) and its correlation with sonographic, prostate size. Material and methods: This cross-sectional study was conducted at Fatima Jinnah Medical University, Lahore from January 2023 to December 2024. Data were collected from 250 patients. Male patients, aged>40 years presented with LUTS were included in the study. Patients with a history of prostate cancer, bladder dysfunction and prostate surgery were excluded from the study. Data were collected through systematically designed questionnaire. All the participants of the study completed the IPSS questionnaire to find the severity and urinary symptoms. Results: Data were collected from 250 patients according to inclusion criteria of the study. Mean age of the patients was 62.4 ± 8.6 years and mean BMI was 27.1 ± 3.2 kg/m2. Mean PSA was 6.8 ± 2.5 ng/mL and mean IPSS score was 19.5 ± 6.8. there were 140 (56%) patients were smoker and 125 (50%) also suffering from hypertension. Patients with IPSS scores ranging from 0-7 exhibited a mean PV of 32.5 ± 5.6 mL, with a Pearson correlation coefficient (r) of 0.25 (p = 0.038). As IPSS scores increased to the 22-35 range, the mean PV rose to 54.3 ± 9.2 mL, accompanied by a stronger correlation coefficient of 0.75 (p < 0.001). Conclusion: It is concluded that there is a significant positive correlation between International Prostate Symptom Score (IPSS) and prostate size in patients with benign prostatic hyperplasia (BPH)